Q: Simplify this expression 4p plus 9 plus-7pplus 2?

Write your answer...

Submit

Related questions

11p+11

4p + 9 - 7p + 2 4p - 7p + 9 + 2 p(4 - 7) + 9 + 2 -3p + 11

It is: 11p+11 simplified

23

4p + 9 + (-7p) + 2 = 4p - 7p + 9 + 2 = -3p + 11

Collect like terms together: 4p + 9 + 7p + 2 = (4p + 7p) + (9 + 2) = (4 + 7)p + 11 = 11p + 11 = 11(p + 1)

4 times p or 4p

5p x 2p = 10p, then 10p / 4p = 2 remainder 2

It is an expression that can be simplified to: 76p-5

The question contains an expression but no equation (or inequality). An expression cannot have an answer.

There is no equation (nor inequality in the question and so there is nothing to solve.The expression can be simplified to 4p - 16 which can be factorised to 4*(p - 4). That is as far as you can go.

It is 820p2 - 4p - 32.

20p that is wrong because it is not an expression

answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}

4p+7q

4p+1 = 10 4p = 10-1 4p = 9 p = 2.25

4p+9-7p+2 -3p+11 p = 11/3

4p+2 = 3p-7 4p-3p = -7-2 p = -9

In order to solve for p, you need to get it alone on one side of the equation4p + 7 = 94p = 2 subtract 7 from both sidesp = 2/4 divide by 4 on each sidep= 1/2 simplify

12p-15+8-4p = 89 12p-4p = 89+15-8 8p = 96 p = 12

2(2p + 5q)

simply add the like terms: 4p -3p +2q -2q = p

15 + 3 = 7p - 4p ie 18 = 3p so p = 6

8p+2=4p-10 8p-4p=-2-10 4p=-12 p=-12/4 =-3

6

Study guides